Characteristics and pathologies of the vitreo‐macular interface—results from the Gutenberg Health Study. Issue 3 (3rd November 2019) - Schuster, Alexander Karl‐Georg; Kluck, Anne‐Kristin; Korb, Christina A.; Stoffelns, Bernhard; Nickels, Stefan; Schulz, Andreas; Münzel, Thomas; Wild, Philipp S.; Beutel, Manfred E.; Schmidtmann, Irene; Lackner, Karl J.; Peto, Tunde; et al.
Abstract: Purpose: We aimed to determine the prevalence of characteristics and pathologies of the vitreo‐macular interface within the general population. Methods: The Gutenberg Health Study is a population‐based study in Germany, including an ophthalmological examination with refraction, biometry and optical coherence tomography (OCT) imaging. Characteristics of the vitreo‐macular interface were graded on volume scans including visibility of an epiretinal membrane, full‐thickness macular hole, lamellar hole and pseudohole. Overall and age‐specific prevalences including 95% confidence intervals [95%‐CI] were calculated. Association analyses were conducted to determine systemic and ocular factors that are associated with epiretinal membranes (the most common pathology) using multivariable logistic regression. Results: A total of 1890 people aged 40–80 years were included in the study. Of these, 4.7% (95%‐CI: 3.8%–5.8%) had an epiretinal membrane in at least one eye, 0.1% a full‐thickness macular hole, 0.6% a lamellar hole and 0.6% a pseudohole. The presence of an epiretinal membrane was associated with higher age, myopic refractive error and prior retinal laser therapy, but not with gender, body height, body weight, smoking, prior cataract surgery or intraocular pressure. Conclusions: Epiretinal membranes are more frequent in older and myopic subjects and in those with prior retinal laser therapy.